(untitled) (Comprehensive Journal of Science, 2025)
This research paper explores the potential of utilizing Autodesk Revit, a Building Information Modeling (BIM) tool, in the documentation of historical buildings, with a focus on Bin Shaaban Palace—a notable heritage site in Libya. The study aims to evaluate Revit’s effectiveness in accurately modeling architectural and structural features of traditional heritage buildings, compared to conventional documentation methods. The methodology involved a detailed on-site architectural survey, followed by the development of a 3D model using Revit, incorporating key architectural, structural, and decorative elements of the palace. The results demonstrated that Revit allows for high-precision digital documentation and facilitates the generation of comprehensive architectural drawings and datasets, which can serve restoration, preservation, and digital presentation purposes. While the use of Revit proved highly efficient, certain limitations were encountered, particularly in modeling irregular traditional elements and the lack of advanced scanning tools such as LiDAR. Nonetheless, the study confirms that BIM tools like Revit offer significant advantages in the heritage conservation field. The paper concludes with a set of recommendations for expanding BIM-based documentation practices in heritage architecture, especially in resource-constrained contexts.